O PROCESSAMENTO DE ORAÇÕES RELATIVAS COM E SEM O PRONOME “THAT” POR BRASILEIROS APRENDIZES TARDIOS DE INGLÊS COMO L21 - Gonçalves, Alyson Andrade; Leitão, Márcio Martins (Organon, 2011)
The purpose of this study is to investigate the linguistic processingof L2 English by a group of Brazilian native speakers. In order to achievethis goal, we analyze the processing of unambiguous object relative clauseswhich contain contrasting structures in the two languages studied here, that is, that have two structure options in English (with or without the pronoun“that”) but only one in Portuguese (containing “that”). Thus, in an onlineself-paced reading experiment, we examined the extent to which Braziliannative speakers would show advantages in processing sentences containingthe relative pronoun “that”, once this structure resembles the one found inPortuguese. Results show that basic, intermediate and advanced learnersseem to process object relative clauses more quickly when they present “that”explicitly, which is taken as an indication of the presence of L1 transfer ef-fects in language processing. Such results are discussed within the predic-tions of the Shallow Structure Hypothesis (Felser et al. 2002).